Development of problem solving-based student worksheets (LKPD) to improve mathematical problem-solving abilities and self-efficacy of junior high school students - Evi Triyana; Anton Jaelani (CV. FOUNDAE, 2026)
Background: Mathematical problem-solving ability and self-efficacy are important components in mathematics learning because they influence students’ capacity to understand problems, apply strategies, and persist in solving challenging tasks. However, many students still experience difficulties in solving contextual mathematical problems, indicating the need for instructional materials that support both cognitive and affective aspects of learning. Aims: This study aims to develop problem-solving-based student worksheets (LKPD) integrated with a contextual sports game setting for learning the Pythagorean Theorem and to evaluate their validity, practicality, and effectiveness in improving students’ mathematical problem-solving ability and mathematics self-efficacy. Method: This study employed a research and development approach using the ADDIE model. The effectiveness of the developed worksheet was examined through a quasi-experimental design involving an experimental group and a control group. Data were collected using expert validation sheets, practicality questionnaires, problem-solving ability tests, and self-efficacy questionnaires, and analyzed using descriptive statistics and independent samples t-tests. Results: The validation results indicated that the worksheet was highly valid (89.5%), while the practicality test showed that it was very practical (89.67%). The effectiveness analysis revealed a significant difference between the experimental and control groups in both mathematical problem-solving ability (t(55) = −6.021, p < .001) and mathematics self-efficacy (t(55) = −2.648, p = .011). Conclusion: The problem-solving-based LKPD with a contextual sports setting is valid, practical, and effective for improving students’ mathematical problem-solving ability and self-efficacy in learning the Pythagorean Theorem.